Development of Teaching-Based Modules Brain Based Learning by Using Games in Mathematics Learning at Yapis Ranting 2 Middle School Timika - hanudin, sub; Herwin, Herwin; Rasul, A. Rasul (Abdi Masyarakat, 2024)
The aim of this research is to determine the feasibility of developing a brain-based learning mathematics module using a crossword puzzle game as seen from the level of validity, practicality and effectiveness. The method used is research and development with the ADDIE research design. This research was conducted at Yapis Ranting 2 Middle School with test subjects of 27 class VIII students. The validity results show that media validation reached a percentage of 83.33% and material validation was 89.98% in the "very valid" category. The module developed is also practical to use with a percentage of teacher response questionnaires of 70.90 with "practical" criteria and student response questionnaires of 81.61% with "very practical" criteria. Furthermore, the effectiveness seen from the results of the posttest with 21 students completing and 6 students not completing received a percentage of 80.76% for the "very effective" criteria. Based on these results, it was concluded that the module developed was suitable for use in learning.